KETERKAITAN PENERAPAN MODEL PEMBELAJARAN BERDIFERENSIASI DAN PENDEKATAN TARL TERHADAP HASIL BELAJAR SISWA DI KELAS: Penelitian Tindakan Kelas - Adira Marsa Yafi Prasasti; Adinda Putri Figi; aminatul fitriyah; Baigia Arta Meifia; Binti Nasiatul Aisiyah; Dra. Repinda Hutasoit, MM; Dr. Sunu Catur Budiyono, M.Hum. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is designed to know relatedness between implementation of differentiate learning model which is collaborated with Teaching at the Right Level approach to the students’ learning achievement at Indonesian subject in XI C - 2 class of 15 Surabaya senior high school. This research is an action class research which is done in two cycles and involved 36 students. The learning have done with content differentiate strategy, process, and product. Also grouping based on cognitive level of the students. The research’s result shows significant improvement in completeness of students’ learning outcomes, from 30,5 percent in pra-cycle to 88,8 percent in second cycle. This findings show that differentiate learning’s model integrated and TaRL approach can improve learning effectiveness also fulfill students’ learning need individually. This strategy is also proven encourage students’ active involvement and improve their learning motivation.